Google Classroom’s Impact on Classroom Management Competencies Among Teacher Educators - Iragamreddy, Venugopal Reddy (Journal of Social Science and Humanities, 2025)
The purpose of this research was to investigate the impact of sixteen weeks Google Classroom training enhancing on Classroom Management skill among Teacher Educators In this experimental study, the Classroom Management skill questionnaire was utilized as research tool. Thirty Teacher Educators from Sri Sarada College of Education were randomly assigned to a group. The training involved daily Google Classroom assessments, which included assignments, quizzes, and materials, conducted for a duration of 20 minutes over sixteen weeks. The group was reassessed after the Sixteen week study period. A pre - test and post - test design was employed to measure changes in Classroom management skill before and after the intervention. The results from the 30 teacher educators indicated a significant increase in Classroom Management skill. Google Classroom on their classroom management and Statistical analysis using a paired sample t - test revealed that the difference in motivation levels was statistically significant (p = 0.001).